Investment Knowledge and Its Impact on Sharia Stock Investment Decisions among Beginner Investors (ISP) in Jember - Dwi Nur An Naafi'u; Mu'awanah Mu'awanah (International Conference on Islamic Economic (ICIE), 2026)
The expansion of Islamic stock investors represents a favorable trend in the growth of the Islamic capital market. Despite this progress, disparities in investment knowledge continue to pose a substantial challenge, particularly for novice investors, as limited understanding may influence the quality and rationality of investment decision-making. This study seeks to investigate the level of sharia stock investment knowledge and examine its effect on investment decisions among Beginner Stock Investors (ISP) in Jember. A quantitative research approach was employed in this study. Data were collected through structured questionnaires administered to all beginner investors who are members of the ISP community in Jember, using a total sampling technique. The collected data were analyzed using SPSS version 22, encompassing validity testing, reliability testing, and classical assumption testing. Descriptive statistical analysis was applied to evaluate the level of sharia stock investment knowledge, while simple linear regression analysis was utilized to assess the influence of investment knowledge on sharia stock investment decisions. The results reveal that the level of sharia stock investment knowledge among Beginner Stock Investors (ISP) in Jember is categorized as very good. Furthermore, the findings demonstrate that investment knowledge exerts a positive and statistically significant influence on sharia stock investment decisions. This indicates that higher levels of investment knowledge contribute to more informed, rational, and appropriate decision-making, particularly in selecting stocks that comply with sharia principles